Trend of genital ulcers and discharge and associated factors among survey respondents in Tanzania, 2004–2022: Analysis of demographic health surveys - Zuhura Mbwana Ally; Lynn Moshi; Rahma Musoke; Mariam Salim Mbwana; Hafidha Mhando Bakari; Swalehe Mustafa Salim; Leticia Francis Karia; Maximillian Francis Karia; Alpha Johnson Kapola; Glenda Marie Manayon; Haji Mbwana Ally; Hassan Fredrick Fussi; et al. (PLoS ONE, 2025)
Introduction Sexually transmitted infections (STIs) continue to pose a significant public health challenge worldwide, with over 1 million new cases reported daily. STI’s are known to negatively impact sexual and reproductive health, increases risk of HIV transmission and acquisitions, as well as impacting mental health, personal wellbeing, and relationships. Information on the trend of STIs using nationally representative data in Tanzania is lacking. We evaluated trends in the prevalence of genital ulcers and discharge using the 2004, 2010 and 2022 Tanzania Demographic Health Survey (TDHS) data. Materials and Methods The TDHS are nationally representative, cross-sectional household surveys that used a two-stage cluster-based sampling design, selecting enumeration areas followed by households. Participants aged 15–49 years who responded to questions on whether they have ever had genital ulcers and/or discharge in the last 12 months prior to the survey were included in this analysis. Survey collected sociodemographic characteristics, HIV testing, STIs symptoms, number of sex partners and recency of sexual activity. We quantified weighted prevalences, and hierarchical mixed effects multilevel logistic regression models that accounted for survey weights, stratification and clustering were used to compute adjusted odds ratios (aOR) and 95% confidence intervals (CI) for factors associated with genital ulcers/discharge. Results Among 46,481 participants with a median age of 27 (interquartile range: 20–36) years, the overall prevalence of genital ulcers/discharge was 6.7%; (4.3% in 2004, 5.0% in 2010 and 9.3% in 2022). Generally, there was an increased trend in genital ulcers/discharge with the increase being higher between 2010 and 2022 compared to 2004 and 2010. In the full adjusted model, females (aOR=1.68: 95%CI 1.48–1.90) had higher odds of genital ulcers/discharge. Divorced/separated/widowed, young individuals, being sexually active 4 weeks prior to the survey and higher number of lifetime sex partners were all associated with higher odds of genital ulcers/discharge. Conclusions There was an increase in the trend of prevalence of genital ulcers/discharge in Tanzania with women and divorced/separated or widowed individuals being disproportionally affected. Identifying reasons for the increase in these STI related symptoms is paramount to strategize and address challenges. Policymakers should prioritize funding for STI diagnostic tools and community education programs. Additionally, healthcare facilities should incorporate routine STI screenings, particularly for high-risk groups like women and those with multiple sexual partners, to curb the rising prevalence.